Clinical Consequences and Economic Burden Associated with Febrile Neutropenia in Hospitalized Cancer Patients: A Prospective Study - Bahar, Tamanna; Rahman, Shaila; Chowdhury, Zulfia Zinat; Kabir, Tania; Akther, Fahmida; Haque, Salina; Islam, AKM Mynul; Ali, Mohammad; Rahman, Md Mahbubur (Journal of Medicine, 2022)
Objective: Febrile neutropenia (FN) is viewed as the most decimating oncological crisis particularly inchemotherapy-incited patients. The primary objective of the study was to identify the total directexpenditure of patients during febrile neutropenia with clinical consequences and the secondary aim wasto find out the factors associated with higher cost. Materials and Method: This was a single-centered hospital-based study in the largest and only specializedcancer care centre in Bangladesh in the government sector. This prospective study was done in theinpatients’ department of the National Institute of Cancer Research and Hospital from April 2020 toJanuary 2021. The primary outcome was the out-of-pocket patient payments (adjusted by governmentsubsidy) per FN episode. Univariate analysis and multiple linear regression were conducted to identifythe factors associated with higher costs. Results and Discussions: A total of 101 patients were enrolled in the study. The mean (SD) age was33.49 (±15.79) years. Of the 101 participants, 63.4% were male. Among the patients, 13.9% died during theepisode and 86.1% recovered. Having co-morbidities and COVID-19 were associated with an increasedrisk of death. The mean cost was US 999.44 (±499.05) and the mean length of hospital stay was 21.98(±9.3) days. The longer hospital stay was significantly associated with higher costs. Conclusion: This study will help to ascertain the hospital cost and clinical outcome of FN whichultimately can help in policymaking strategy. J MEDICINE 2022; 23: 48-53